Analysis of the Relationship Between Resistivity and Seawater Moisture Content Percentage in Loose Sand Medium on the Yogyakarta Coastal Area - Pratama, Yudha Agung; Paradise, Mycelia; Suharsono, Suharsono; Hidayat, Wahyu; Setiahadiwibowo, Ajimas Pascaning (Indonesian Journal of Earth Sciences, 2025)
This study investigates the effect of seawater moisture content on the resistivity of unconsolidated sand in the coastal region of Yogyakarta. Laboratory experiments were conducted using a standard ASTM G-57 soil box with samples prepared at varying percentages of seawater moisture content. The results indicate that increasing seawater content in the sediment medium leads to an exponential decrease in resistivity. A mathematical relationship was established in the form of a power function: R=1145.7MC?2.23. Resistivity values tend to stabilize when the moisture content exceeds 13%. A resistivity range of 0.8–2.8 ??m is proposed as a cut-off for identifying seawater intrusion in coastal areas. These findings provide an important contribution to the development of geoelectrical methods for monitoring seawater intrusion and evaluating groundwater quality in coastal regions, which can serve as a basis for sustainable water resource management.